Secondary battery and electronic device

By using graphite and highly spherical silicon carbon materials in the negative electrode sheet of the secondary battery and adjusting the component ratio in the electrolyte, the poor performance of the secondary battery under high and low temperature conditions is solved, and the load is significantly improved Electrical retention capability, low temperature discharge performance and safety performance.

CN119447178AActive Publication Date: 2025-02-14NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202510034508.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-14
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The performance of existing secondary batteries under high and low temperature conditions is poor, especially the charge retention ability and short-circuit test pass rate, which affects its safety performance.

Method used

By using graphite and highly spherical silicon carbon materials in the negative electrode sheet and adjusting the ratio of vinyl carbonate, propylene carbonate, ethyl propionate and propyl propionate in the electrolyte, the intercalation/exit rate of active ions is improved. and transmission paths to improve the battery's charge retention capability and low-temperature discharge performance, while enhancing short-circuit test pass rate and safety performance.

Benefits of technology

It significantly improves the discharge performance and short-circuit test pass rate of the secondary battery at low temperatures, and improves the safety performance and charge retention ability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a secondary battery and electronic equipment, the secondary battery comprises a negative electrode plate and an electrolyte, the negative electrode plate comprises a negative electrode active material layer, the negative electrode active material layer comprises graphite and a silicon carbon material, and the average sphericity of the silicon carbon material is 0.81-0.95; the electrolyte comprises ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate, based on the mass of the electrolyte, the mass percentage content of ethylene carbonate is a%, the mass percentage content of propylene carbonate is b%, the mass percentage content of ethyl propionate is c%, the mass percentage content of propyl propionate is d%, and the range of (a + b) / (c + d) is 0.23-1.51. According to the invention, the discharge performance and the safety performance of the secondary battery at low temperature can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electronic device including the secondary battery. Background Art

[0002] Secondary batteries, such as lithium-ion batteries, have the advantages of being environmentally friendly, having high energy density, and having a long cycle life. They are widely used in mobile phones, computers, wearable devices, consumer drones, power tools, electric motorcycles, electric vehicles, or large energy storage devices. As the market continues to expand, the performance requirements for secondary batteries have also been continuously improved, such as the performance of batteries under high and low temperature conditions. At present, carbonate compounds are often used as solvent systems for the electrolyte of secondary batteries, but this type of secondary battery has poor high voltage stability and is prone to cause structural instability of the graphite material of the negative electrode, reducing its electrochemical performance. Therefore, the performance of secondary batteries needs to be further improved. Summary of the invention

[0003] In view of this, the present application provides a secondary battery and an electronic device, which can improve the charge retention capability of the secondary battery, thereby improving the low-temperature discharge performance of the secondary battery, and improving the short-circuit test pass rate of the secondary battery, thereby improving the safety performance of the secondary battery.

[0004] In a first aspect, the present application provides a secondary battery, comprising a negative electrode plate and an electrolyte, wherein the negative electrode plate comprises a negative electrode active material layer, the negative electrode active material layer comprises graphite and a silicon-carbon material, and the average sphericity of the silicon-carbon material is 0.81 to 0.95; the electrolyte comprises ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate, and based on the mass of the electrolyte, the mass percentage of ethylene carbonate is a%, the mass percentage of propylene carbonate is b%, the mass percentage of ethyl propionate is c%, and the mass percentage of propyl propionate is d%, wherein the range of (a+b) / (c+d) is 0.23 to 1.51. The electrolyte with the above-mentioned specific components can increase the embedding / de-embedding rate of active ions on the surface of highly spherical silicon-carbon materials, shorten the transmission path of active ions between graphite and silicon-carbon materials, and improve its charge retention ability while maintaining high battery capacity, thereby improving the discharge performance of secondary batteries at low temperatures. At the same time, the migration rate of active ions is improved, which can reduce the lithium dendrites generated on the surface of the electrode, increase the short-circuit test pass rate of secondary batteries, and improve the safety performance of secondary batteries.

[0005] Based on the content of the first aspect, in some embodiments, the electrolyte further comprises 1,3,6-hexane trinitrile, and the mass percentage of 1,3,6-hexane trinitrile is e%, based on the mass of the electrolyte, and the range of (a+b) / e is 4 to 18.5. In some embodiments, the range of (a+b) / e is 5.1 to 15. It can improve the transmission of active ions between graphite and silicon-carbon materials, further improve the discharge performance of the secondary battery at low temperature, improve the short-circuit test pass rate of the secondary battery, and improve the safety performance of the secondary battery.

[0006] Based on the content of the first aspect, in some embodiments, based on the mass of the electrolyte, the mass percentage of the 1,3,6-hexanetricarbonitrile is 0.8% to 4.3%; in some embodiments, the mass percentage of the 1,3,6-hexanetricarbonitrile is 1.3% to 3.5%; the discharge performance and safety performance of the secondary battery at low temperatures can be further improved.

[0007] Based on the content of the first aspect, in some embodiments, the electrolyte further includes at least one of fluoroethylene carbonate, succinonitrile, ethylene glycol bis(propionitrile) ether, lithium difluorophosphate and or lithium tetrafluoroborate. The electrolyte containing the above substances can form a highly ion-conductive protective film on the surface of the graphite material and the silicon-carbon material with high sphericity, further promoting the rapid transmission of active ions on the surface of the negative electrode active material, thereby facilitating the improvement of the discharge performance and safety performance of the secondary battery at low temperatures.

[0008] Based on the content of the first aspect, in some embodiments, the mass percentage of fluoroethylene carbonate is 0.5% to 3.9%; the mass percentage of fluoroethylene carbonate within the above range is conducive to the formation of a high-ion conductivity protective film with an appropriate content, and is conducive to improving the stability of the surface of the negative electrode plate, and further improving the discharge performance and safety performance of the secondary battery at low temperatures.

[0009] Based on the content of the first aspect, in some embodiments, the mass percentage of succinonitrile is 0.6% to 3.9%; in some embodiments, the mass percentage of succinonitrile is 1.3% to 3.2%; the mass percentage of succinonitrile within the above range is conducive to the formation of a high-ion conductive protective film with an appropriate content, further improving the discharge performance and safety performance of the secondary battery at low temperatures.

[0010] Based on the content of the first aspect, in some embodiments, the mass percentage of ethylene glycol bis(propionitrile) ether is 0.2% to 2.5%; the mass percentage of ethylene glycol bis(propionitrile) ether within the above range is beneficial to inhibiting the increase of surface defects of high-sphericity silicon-carbon materials, increasing the active ion transfer rate, and further improving the discharge performance and safety performance of secondary batteries at low temperatures.

[0011] Based on the content of the first aspect, in some embodiments, the mass percentage of lithium difluorophosphate is 0.01% to 0.30%; the mass percentage of lithium difluorophosphate within the above range helps to stabilize the defect structure on the surface of high-sphericity silicon-carbon materials, promote the transmission of active ions, and further improve the discharge performance and safety performance of secondary batteries at low temperatures.

[0012] Based on the content of the first aspect, in some embodiments, the mass percentage of lithium tetrafluoroborate is 0.001% to 0.100%. The mass percentage of lithium tetrafluoroborate within the above range is conducive to further improving the surface ion pathway of the silicon-carbon material with high sphericity, promoting the rapid transmission of active ions, and further improving the discharge performance and safety performance of the secondary battery at low temperatures.

[0013] Based on the content of the first aspect, in some embodiments, the electrolyte further comprises lithium difluorophosphate, and based on the mass of the electrolyte, the mass percentage of lithium difluorophosphate is n%, and n satisfies the relationship with the average sphericity m of the silicon-carbon material: the range of m / n is 3 to 14.5. In some embodiments, the range of m / n is 3.9 to 12.7. This allows lithium difluorophosphate to fully stabilize the defect structure on the surface of the high-sphericity silicon-carbon material, facilitate the rapid transmission of active ions on the surface of the silicon-carbon material, reduce the occurrence of side reactions, further enhance the charge retention capacity of the secondary battery, improve the discharge performance of the secondary battery at low temperatures, and increase the short-circuit test pass rate of the secondary battery, thereby enhancing the safety performance of the secondary battery.

[0014] Based on the content of the first aspect, in some embodiments, the mass percentage of fluoroethylene carbonate is 1.1% to 3.2%, which is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0015] Based on the content of the first aspect, in some embodiments, a ranges from 10 to 38; in some embodiments, a ranges from 11 to 26; this is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0016] Based on the content of the first aspect, in some embodiments, the range of b is 5 to 26; in some embodiments, the range of b is 7 to 20; which is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0017] Based on the content of the first aspect, in some embodiments, c ranges from 12 to 26, and in some embodiments, c ranges from 13 to 21; this is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0018] Based on the content of the first aspect, in some embodiments, d ranges from 27 to 53, and in some embodiments, d ranges from 30 to 44; this is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0019] Based on the content of the first aspect, in some embodiments, the range of e is 0.8 to 4.3, which is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures in some embodiments.

[0020] Based on the content of the first aspect, in some embodiments, based on the mass of the electrolyte, the mass percentage of lithium difluorophosphate is 0.04% to 0.24%, which is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0021] Based on the content of the first aspect, in some embodiments, based on the mass of the electrolyte, the mass percentage of ethylene glycol bis(propionitrile) ether is 0.4% to 2.1%, which is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0022] Based on the content of the first aspect, in some embodiments, based on the mass of the electrolyte, the mass percentage of lithium tetrafluoroborate is 0.008% to 0.050%, which is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures.

[0023] The second aspect of the present application provides an electronic device, comprising the secondary battery described in any one of the first aspects. The secondary battery is used as a power source for the electronic device, and the secondary battery has stable performance and can stably power the electronic device.

[0024] Compared with the prior art, this application has the following beneficial effects: The present application provides a secondary battery, which includes a positive electrode, a negative electrode and an electrolyte. The negative electrode plate includes a negative electrode active material layer, the negative electrode active material layer includes graphite and silicon-carbon material, and the average sphericity of the silicon-carbon material is 0.81 to 0.95; the electrolyte includes ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate. Based on the mass of the electrolyte, the mass percentage of ethylene carbonate is a%, the mass percentage of propylene carbonate is b%, the mass percentage of ethyl propionate is c%, and the mass percentage of propyl propionate is d%, wherein the range of (a+b) / (c+d) is 0.23 to 1.51. The high average sphericity of the silicon-carbon material combined with the relationship between the mass percentages of ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate in the electrolyte can improve the low-temperature discharge performance and safety performance of the secondary battery during short circuit. DETAILED DESCRIPTION

[0025] The technical scheme in the embodiment of the present application is clearly and in detail described below, and it is obvious that the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. Unless otherwise defined, all technical and scientific terms used herein are identical with the meanings generally understood by the technicians in the technical field belonging to the present application. The term used in the specification of the application is only for the purpose of describing specific embodiments, and is not intended to limit the application. The data range values ​​recorded in the application should include end values ​​unless otherwise specified.

[0026] The present application provides a secondary battery, including a negative electrode plate and an electrolyte, the negative electrode plate includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite and silicon-carbon material, and the average sphericity of the silicon-carbon material is 0.81 to 0.95; the electrolyte includes ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate, based on the mass of the electrolyte, the mass percentage of ethylene carbonate is a%, the mass percentage of propylene carbonate is b%, the mass percentage of ethyl propionate is c%, and the mass percentage of propyl propionate is d%, wherein the range of (a+b) / (c+d) is 0.23 to 1.51.

[0027] In the present application, the negative electrode plate in the secondary battery includes graphite and silicon-carbon material, the sphericity of the silicon-carbon material is within the above range, and when the content of ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate in the electrolyte meets the above range, the electrolyte with the above specific components can increase the rate of embedding / extraction of active ions on the surface of the silicon-carbon material with high sphericity, and can shorten the transmission path of active ions between graphite and silicon-carbon material, so that the secondary battery can maintain the high capacity of the secondary battery while improving its charge retention ability; thereby improving the discharge performance of the secondary battery at low temperature, and at the same time, the improvement of the migration rate of active ions inside the secondary battery can reduce the lithium dendrites generated on the surface of the electrode plate, thereby improving the short-circuit test pass rate of the secondary battery to improve the safety performance of the secondary battery.

[0028] In some embodiments, the average sphericity of the silicon-carbon material can be 0.81, 0.83, 0.85, 0.87, 0.89, 0.90, 0.91, 0.93, 0.95, or any value within the range formed by any two of the above values. In some embodiments, the ratio of (a+b) / (c+d) can be 0.23, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.51, or any value within the range formed by any two of the above values.

[0029] If the ratio of (a+b) / (c+d) is small, such as less than 0.23, the sum of the mass percentages of ethyl propionate and propyl propionate is large, and the above two are prone to side reactions, affecting the interface stability between the electrode and the electrolyte in the secondary battery, or the content of ethylene carbonate and propylene carbonate is small, which may affect the overall stability of the secondary battery, thereby affecting the short-circuit test pass rate of the secondary battery and affecting the safety performance of the secondary battery; if the ratio of (a+b) / (c+d) is large, such as greater than 1.51, the sum of the mass percentages of ethyl propionate and propyl propionate is small, which will affect the transmission rate of active ions between graphite and silicon-carbon materials, thereby affecting the low-temperature discharge performance of the secondary battery. In some embodiments, the electrolyte further contains 1,3,6-hexane trinitrile, based on the mass of the electrolyte, the mass percentage of 1,3,6-hexane trinitrile is e%, and the range of (a+b) / e is 4 to 18.5. When the content of 1,3,6-hexane trinitrile and the sum of the contents of ethylene carbonate and propylene carbonate meet the above range, the transmission of active ions between graphite and silicon-carbon materials can be improved, the discharge performance of the secondary battery at low temperature can be further improved, the short-circuit test pass rate of the secondary battery can be improved, and the safety performance of the secondary battery can be improved. In some embodiments, the ratio of (a+b) / e can be 4, 4.5, 5, 5.1, 5.5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 15.5, 16, 17, 18, 18.5 or any value within the range of any two of the above values. Preferably, the range of (a+b) / e is 5.1 to 15, which can further improve the performance of the secondary battery.

[0030] In some embodiments, the electrolyte further comprises at least one of fluoroethylene carbonate, succinonitrile, ethylene glycol bis(propionitrile) ether, lithium difluorophosphate or lithium tetrafluoroborate. The electrolyte comprising the above substances can form a highly ion-conductive protective film on the surface of the graphite material and the silicon-carbon material with high sphericity, further promoting the rapid transmission of active ions on the surface of the negative electrode active material, thereby facilitating the improvement of the discharge performance and safety performance of the secondary battery at low temperatures.

[0031] In some embodiments, based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 0.5% to 3.9%. The mass percentage of fluoroethylene carbonate within the above range is conducive to the formation of a high ion conductivity protective film of an appropriate content, and is conducive to improving the stability of the surface of the negative electrode plate, and further improving the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, the mass percentage of fluoroethylene carbonate can be 0.5%, 0.8%, 1%, 1.2%, 1.8%, 2.1%, 2.3%, 2.5%, 2.7%, 3%, 3.2%, 3.3%, 3.5%, 3.9% or any value within the range of any two of the above values. In some embodiments, based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate (FEC) is 0.8% to 3.2%. Preferably, the mass percentage of fluoroethylene carbonate is 1.1% to 3.2%. It is conducive to further improving the discharge performance and safety performance of the secondary battery at low temperatures.

[0032] In some embodiments, based on the mass of the electrolyte, the mass percentage of succinonitrile is 0.6% to 3.9%. The mass percentage of succinonitrile within the above range is conducive to forming a high ion-conducting protective film of an appropriate content, further improving the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, the mass percentage of succinonitrile can be 0.6%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.1%, 3.3%, 3.5%, 3.9% or any value within the range of any two of the above values. Preferably, the mass percentage of succinonitrile is 1.3% to 3.2%.

[0033] In some embodiments, based on the mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether is 0.2% to 2.5%. The mass percentage of ethylene glycol bis (propionitrile) ether is within the above range, which is beneficial to suppress the increase of surface defects of silicon-carbon materials with high sphericity, improve the active ion transfer rate, and further improve the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, the mass percentage of ethylene glycol bis (propionitrile) ether can be 0.2%, 0.3%, 0.4%, 0.5%, 0.7%, 1%, 1.5%, 1.7%, 2%, 2.1%, 2.3%, 2.5% or any value within the range of any two of the above values. Preferably, the mass percentage of ethylene glycol bis (propionitrile) ether is 0.4% to 2.1%.

[0034] In some embodiments, based on the mass of the electrolyte, the mass percentage of lithium difluorophosphate is 0.01% to 0.30%. The mass percentage of lithium difluorophosphate within the above range helps to stabilize the defective structure on the surface of the silicon-carbon material with high sphericity, promotes the transmission of active ions, and further improves the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, the mass percentage of lithium difluorophosphate can be 0.01%, 0.03%, 0.04%, 0.05%, 0.08%, 0.10%, 0.15%, 0.18%, 0.20%, 0.24%, 0.25%, 0.28%, 0.30% or any value within the range of any two of the above values. Preferably, the mass percentage of lithium difluorophosphate is 0.04% to 0.24%.

[0035] In some embodiments, based on the mass of the electrolyte, the mass percentage of lithium tetrafluoroborate is 0.001% to 0.100%. The mass percentage of lithium tetrafluoroborate within the above range is conducive to further improving the surface ion path of silicon-carbon materials with high sphericity, promoting the rapid transmission of active ions, and further improving the discharge performance and safety performance of secondary batteries at low temperatures. In some embodiments, the mass percentage of lithium tetrafluoroborate can be 0.001%, 0.003%, 0.005%, 0.008%, 0.010%, 0.020%, 0.030%, 0.040%, 0.050%, 0.060%, 0.070%, 0.080%, 0.090%, 0.100% or any value within the range of any two of the above values. Preferably, the mass percentage of lithium tetrafluoroborate is 0.008% to 0.050%.

[0036] In some embodiments, the electrolyte further comprises lithium difluorophosphate, and based on the mass of the electrolyte, the mass percentage of lithium difluorophosphate is n%, and n satisfies the relationship with the average sphericity m of the silicon-carbon material: the range of m / n is 3 to 14.5, and the content of lithium difluorophosphate and the average sphericity of the silicon-carbon material satisfy the above relationship, so that lithium difluorophosphate can fully stabilize the defect structure on the surface of the high-sphericity silicon-carbon material, facilitate the rapid transmission of active ions on the surface of the silicon-carbon material, reduce the occurrence of side reactions, further improve the charge retention ability of the secondary battery, improve the discharge performance of the secondary battery at low temperatures, and improve the short-circuit test pass rate of the secondary battery, and improve the safety performance of the secondary battery. In some embodiments, m / n can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 14.5 or any value within the range of any two of the above values. Preferably, the range of m / n is 3.9 to 12.7, which further improves the performance of the secondary battery.

[0037] In some embodiments, based on the mass of the electrolyte, the mass percentage of ethylene carbonate is a%, and the range of a is 10 to 38. In some embodiments, the range of a is 11 to 26. In some embodiments, the range of a is 11 to 22. It is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, a can be 10, 12, 15, 17, 19, 20, 22, 25, 28, 30, 32, 34, 36, 37, 38 or any value within the range of any two of the above values.

[0038] In some embodiments, based on the mass of the electrolyte, the mass percentage of propylene carbonate is b%, and the range of b is 5 to 26. In some embodiments, the range of b is 7 to 20. In some embodiments, the range of b is 9 to 20. It is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, b can be 5, 8, 10, 12, 15, 17, 20, 24, 26 or any value within the range of any two of the above values.

[0039] In some embodiments, based on the mass of the electrolyte, the mass percentage content of ethyl propionate c%, c ranges from 12 to 26; in some embodiments, c ranges from 13 to 21. In some embodiments, c ranges from 13 to 19. It is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, c can be 12, 15, 17, 19, 20, 21, 22, 25, 26 or any value within the range formed by any two of the above values.

[0040] In some embodiments, based on the mass of the electrolyte, the mass percentage content of propyl propionate is d%, and the range of d is 27 to 49. In some embodiments, the range of d is 30 to 45. In some embodiments, the range of d is 31 to 43. It is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, d can be 27, 29, 31, 34, 37, 40, 43, 47, 49 or any value within the range of any two of the above values.

[0041] In some embodiments, based on the mass of the electrolyte, the mass percentage content of 1,3,6-hexanetrinitrile is e%, and the range of e is 0.8 to 4.3; in some embodiments, the range of e is 1.3 to 3.5. It is beneficial to further improve the discharge performance and safety performance of the secondary battery at low temperatures. In some embodiments, e can be 0.8, 1.2, 1.5, 1.8, 2, 2.4, 2.8, 3, 3.4, 3.8, 4, 4.3 or any value within the range formed by any two of the above values.

[0042] The second aspect of the present application provides an electronic device, comprising the above-mentioned secondary battery. The above-mentioned secondary battery is used as a power source for the electronic device, and the secondary battery has stable performance and can stably power the electronic device.

[0043] Electrolyte In addition to the above-mentioned ethyl propionate and propyl propionate, the organic solvent in the electrolyte also includes some other organic solvents, which may be but are not limited to: diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or dimethyl carbonate (DMC). In some embodiments, the other organic solvent includes an ether solvent, for example, at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME).

[0044] In the embodiment of the present application, the electrolyte includes a lithium salt as an electrolyte. The lithium salt in the electrolyte includes, but is not limited to: inorganic lithium salts, such as LiClO4, LiAsF6, LiPF6, LiSbF6, LiSO3F, LiN(FSO2)2; fluorine-containing organic lithium salts, such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, LiPF4(CF3)2, LiN(CF3SO2)(C4 F9SO2), LiC(CF3SO2)3, LiPF4(CF3SO2)2, LiPF4(C2F5)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate. In addition, the above-mentioned lithium salts can be used alone or in combination of two or more. For example, in some embodiments, the lithium salt comprises a combination of LiPF6 and LiBF4. In some embodiments, the lithium salt comprises LiPF6. In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium salt in the electrolyte is 9% to 15%.

[0045] The preparation method of the electrolyte of the embodiment of the present application is not limited, and can be prepared in the manner of a conventional electrolyte. In some embodiments, the electrolyte of the present application can be prepared by mixing the components.

[0046] negative electrode In some embodiments, the graphite includes at least one of artificial graphite or natural graphite.

[0047] Graphite can be obtained by the following method: some petroleum coke with relatively low volatility is selected as a raw material, crushed into single particles, and after it is converted into graphite through heat treatment, surface modification treatment is performed to finally obtain negative electrode active particles. Of course, the preparation method of the negative electrode active particles is not limited to this, but can also be prepared by other methods well known in the art.

[0048] In some embodiments, the silicon-carbon material can be obtained by the following preparation method: preparing it by using a porous carbon material as a skeleton and then depositing silicon; preferably, the preparation of the silicon-carbon material includes the following steps: subjecting the porous carbon skeleton to a silane deposition reaction to obtain a precursor material, and micro-oxidizing the precursor material to obtain the silicon-carbon material.

[0049] In some embodiments, the average sphericity of the silicon-carbon material can be regulated by a particle shaping process. The particle shaping process can be performed using any one of a turbine pulverizer, an air vortex micronizer, a super cyclone vortex mill, an air separation pulverizer, or a double-roll pulverizer. By using the above equipment and controlling the equipment speed and processing time, particle shaping can be achieved to obtain the desired average sphericity.

[0050] In some embodiments, the negative electrode active material layer further comprises a binder. The binder may include various binder polymers, such as polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0051] In some embodiments, the negative electrode active material layer further comprises a conductive agent to improve the electrode conductivity. Any conductive material can be used as the conductive material as long as it does not cause chemical changes. Examples of conductive agents include, but are not limited to: carbon-based materials, such as carbon black, acetylene black, Ketjen black, carbon fibers, etc.; metal-based materials, such as metal powders or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives, etc.; or mixtures thereof.

[0052] In some embodiments, the negative electrode current collector includes, but is not limited to: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with conductive metal, and any combination thereof. In some embodiments, the negative electrode current collector is copper foil.

[0053] In some embodiments, the structure of the negative electrode is a negative electrode structure known in the art and can be used in an electrochemical device.

[0054] In some embodiments, the preparation method of the negative electrode is a method for preparing a negative electrode that can be used for an electrochemical device that is well known in the art. Exemplarily, the negative electrode can be obtained by the following method: mixing the active material, the conductive agent, the binder and the above-mentioned negative electrode additive in a solvent, and heating the thickener as needed to prepare a negative electrode active material slurry, and coating the negative electrode active material slurry on the current collector, drying, and cold pressing to form a negative electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water, N-methylpyrrolidone.

[0055] positive electrode The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The specific types of the positive electrode active material are not subject to specific restrictions and can be selected according to needs.

[0056] In some embodiments, the positive electrode active material includes a lithium transition metal composite oxide. In some embodiments, the positive electrode active material is selected from at least one of the following: lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or lithium iron phosphate (LiFePO4).

[0057] In some embodiments, the positive electrode active material layer further includes a binder and optionally a conductive material. The binder can improve the bonding between the positive electrode active material particles and can improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon, etc.

[0058] In some embodiments, the positive electrode active material layer also includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0059] In some embodiments, the positive electrode current collector is a metal, such as but not limited to aluminum foil.

[0060] In some embodiments, the structure of the positive electrode is a positive electrode structure known in the art that can be used in a secondary battery.

[0061] In some embodiments, the preparation method of the positive electrode is a preparation method of the positive electrode that can be used for a secondary battery that is well known in the art. For example, the positive electrode can be obtained by the following method: mixing the active material, the conductive material, the binder and the above-mentioned positive electrode additive in a solvent to prepare a positive electrode active material slurry, and coating the positive electrode active material slurry on the current collector, drying, and cold pressing to form a positive electrode active material layer. In some embodiments, the solvent may include water, N-methylpyrrolidone, etc., but is not limited thereto.

[0062] Isolation film In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0063] For example, in some embodiments, the isolation film includes a substrate layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure. The material of the substrate layer can be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer can be selected from polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film.

[0064] A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer can be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic substance. Specifically, the inorganic layer includes inorganic particles and a binder. The inorganic particles can be selected from one or more combinations of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder can be selected from one or more combinations of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0065] According to a second aspect of the present application, the present application provides an electronic device, which includes the above-mentioned secondary battery.

[0066] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc. In addition, the secondary battery of the present application is applicable to energy storage power stations, sea transport vehicles, and air transport vehicles in addition to the electronic devices listed above. Air transport vehicles include air transport vehicles within the atmosphere and air transport vehicles outside the atmosphere.

[0067] The technical solution of the embodiment of the present application is further illustrated by means of specific examples below.

[0068] Example 1-1 1. Preparation of lithium-ion batteries: 1. Preparation of negative electrode The negative electrode active material is artificial graphite and silicon-carbon material, wherein the sphericity of the silicon-carbon material is 0.89. The preparation process of the silicon-carbon material is as follows: Providing a porous carbon framework: the pore volume of the porous carbon framework is 0.7 g / cc, wherein the pore volume of micropores and mesopores is 82%; The porous carbon skeleton was subjected to a silane deposition reaction, and the conditions of the silane deposition reaction included: at 700°C, silane gas with a volume content of 24% was introduced, and the other gas component was nitrogen, and the reaction time was 10 hours to obtain a precursor material; the precursor material was subjected to a 20% volume content of oxygen, and the other gas component was nitrogen, and the reaction time was 15 hours to obtain a silicon-carbon material. Then, the silicon-carbon material was shaped using a turbine pulverizer, and the average sphericity of the silicon-carbon material was 0.89.

[0069] Artificial graphite, the silicon-carbon material, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are added to the solvent deionized water at a mass ratio of 90:5:1.8:1.5:1.7, and stirred and mixed thoroughly to form a uniform negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried, and cold pressed to form a negative electrode active material layer, and then cut into pieces and welded to the pole ears to obtain a negative electrode sheet.

[0070] 2. Preparation of positive electrode The positive electrode active material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.3:2.2:1.5, and fully stirred in a vacuum mixer to obtain a positive electrode slurry. The positive electrode material is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to form a positive electrode active material layer, and then cut into pieces and welded to the pole ears to obtain a positive electrode sheet.

[0071] 3. Preparation of electrolyte In a dry argon atmosphere glove box, propyl propionate (PP), ethyl propionate (EP), ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate are mixed evenly, dissolved and fully stirred, and then lithium salt LiPF6 is added, and the electrolyte is obtained after mixing evenly. Wherein, based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12%, the mass percentage of EP is 13%, the mass percentage of PP is 41%, the mass percentage of EC is 11%, the mass percentage of PC is 20%, and (a+b) / (c+d) is 0.57. Wherein, in some embodiments, diethyl carbonate is not added to the electrolyte.

[0072] 4. Preparation of Isolation Membrane Polyethylene (PE) porous polymer film is used as the isolation membrane with a porosity of 30%.

[0073] 5. Preparation of Lithium-ion Batteries The obtained positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging foil aluminum-plastic film, and the electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation and other process flows.

[0074] Example 1-2 to Example 1-24 The differences between the preparation processes of Examples 1-2 to 1-24 and Example 1-1 are listed in Table 1, wherein Examples 1-10 and 1-16 do not contain diethyl carbonate, and the average sphericity of the silicon-carbon materials in Examples 1-17 to 1-24 is obtained by adjusting the speed and processing time of the turbine mill. The remaining preparation processes and conditions are the same as those of Example 1-1.

[0075] Comparative Example 1-1 to Comparative Example 1-3 The differences between the preparation processes of Comparative Examples 1-1 to 1-3 and Example 1-1 are listed in Table 1. Comparative Example 1-1 does not contain diethyl carbonate. The remaining preparation processes and conditions are the same as those of Example 1-1.

[0076] Example 2-1 to Example 2-13 The differences between the preparation processes of Examples 2-1 to 2-13 and Example 1-3 are listed in Table 2, and the effects of adjusting the mass percentage of EC, PC, EP, PP and 1,3,6-hexanetrinitrile in the electrolyte on the low-temperature discharge maintenance rate and short-circuit test pass rate of the lithium-ion battery. The rest of the preparation process and conditions are the same as those of Example 1-3.

[0077] Example 3-1 to Example 3-29 The differences between the preparation processes of Examples 3-1 to 3-29 and Example 1-3 are listed in Table 3, and the mass percentages of fluoroethylene carbonate, succinonitrile, ethylene glycol bis(propionitrile) ether, lithium difluorophosphate and lithium tetrafluoroborate in the electrolyte are adjusted. The rest of the preparation process and conditions are the same as those of Example 1-3.

[0078] Example 3-30 to Example 3-33 The differences between the preparation processes of Examples 3-30 to 3-33 and Example 2-2 are listed in Table 4, and the mass percentages of fluoroethylene carbonate, succinonitrile, ethylene glycol bis(propionitrile) ether, lithium difluorophosphate and lithium tetrafluoroborate in the electrolyte are adjusted. The rest of the preparation process and conditions are the same as those of Example 2-2.

[0079] Example 4-1 to Example 4-11 The differences between the preparation processes of Examples 4-1 to 4-11 and Example 1-3 are listed in Table 5, and the average sphericity of the silicon-carbon material and the mass percentage of lithium difluorophosphate are adjusted. The rest of the preparation process and conditions are the same as those of Example 1-3.

[0080] For specific differences among Examples 1-2 to 1-24, Examples 2-1 to 2-13, Examples 3-1 to 3-33, and Examples 4-1 to 4-11, see Detailed Tables 1 to 5.

[0081] 2. Test Method Electrolyte component test: The electrolyte was tested by gas chromatography-mass spectrometry (GC-MS) and ion chromatography (IC) to detect various components in the electrolyte and test their contents.

[0082] Sphericity test: 3g of dispersed silicon-carbon material particles were captured and processed using a Malvern automatic image particle size analyzer. Image-guided Raman spectroscopy (MDRS) was then used to accurately analyze the microstructure and morphology of the particles, and the longest and shortest diameters of all particles were obtained. The ratio of the shortest diameter to the longest diameter of each particle was calculated to obtain the sphericity of each particle. The average sphericity of all particles was taken as the average sphericity.

[0083] Low temperature discharge performance At 25°C, the lithium-ion battery is charged to 4.25V at a constant current of 1.0C, and then charged at a constant voltage until the current drops to 0.05C; the temperature is lowered to -10°C, left for 30 minutes, and then discharged to 3.0V at a constant current of 1.0C; the initial discharge capacity at -10°C is obtained; At 60°C, the lithium-ion battery was charged to 4.25V at a constant current of 1.0C, then charged at a constant voltage until the current dropped to 0.05C, and the lithium-ion battery was stored for 2 days; the temperature was lowered to -10°C, left for 30 minutes, and then discharged to 3.0V at a constant current of 1.0C; the discharge capacity at -10°C after high temperature storage was obtained; Low-temperature discharge maintenance rate = (discharge capacity at -10°C after high-temperature storage / initial discharge capacity at -10°C) × 100%.

[0084] Short circuit test pass rate Charge at 1.0C constant current to 4.2V, then charge at constant voltage until the current drops to 0.05C, then stop charging; let stand for 1 hour, then measure OCV; short-circuit the positive and negative electrodes of the lithium-ion battery with a copper wire with a resistance of no more than 0.1 ohm at room temperature; the lithium-ion battery is discharged until it catches fire or explodes or until the lithium-ion battery is fully discharged, and the test can be stopped when the surface temperature of the lithium-ion battery returns to a temperature close to the ambient temperature. 20 lithium-ion batteries are tested, and the number of lithium-ion batteries that meet the judgment criteria is counted as the short-circuit test pass rate of the lithium-ion battery; Judgment criteria: the battery does not leak, smoke, catch fire, or explode, and the battery surface temperature does not exceed 150℃.

[0085] Table 1 In Table 1, the mass percentage of EC, PC, EP, PP in the electrolyte, and / or the average sphericity of the silicon-carbon material are adjusted to study their effects on the low-temperature discharge maintenance rate and short-circuit test pass rate of the lithium-ion battery. In Table 1, compared with Comparative Examples 1-1 to 1-3, in Examples 1-1 to 1-16, when propyl propionate (PP), ethyl propionate (EP), ethylene carbonate (EC), propylene carbonate (PC) or part of diethyl carbonate is evenly mixed, the silicon-carbon material has a high sphericity and the range of (a+b) / (c+d) is within an appropriate range, and the lithium-ion battery assembled therefrom has good low-temperature discharge performance and a short-circuit test pass rate. In particular, it can be seen from Examples 1-17 to 1-24 that when the silicon-carbon material has a high sphericity, it also significantly improves the lithium-ion battery's good low-temperature discharge performance and short-circuit test pass rate.

[0086] Table 2 In Table 2, the mass percentages of EC, PC, EP, PP and 1,3,6-hexane trinitrile in the electrolyte are adjusted to study their effects on the low temperature discharge maintenance rate and short circuit test pass rate of the lithium ion battery. In the above-mentioned Examples 2-2 to 2-13, when the silicon-carbon material has a high sphericity, the electrolyte contains an appropriate amount of 1,3,6-hexane trinitrile, and when ethylene carbonate, propylene carbonate and 1,3,6-hexane trinitrile meet a specific relationship range, the lithium ion battery has good low temperature discharge performance and a short circuit test pass rate.

[0087] Table 3 Table 4 In Table 3 and Table 4, the mass percentage of fluoroethylene carbonate, succinonitrile, ethylene glycol bis (propionitrile) ether, lithium difluorophosphate and lithium tetrafluoroborate in the electrolyte is adjusted to study its influence on the battery low temperature discharge maintenance rate and short circuit test pass rate. In the above-mentioned embodiments 3-1 to 3-29, when the silicon-carbon material has a high sphericity, and when the electrolyte contains at least one of fluoroethylene carbonate, succinonitrile, ethylene glycol bis (propionitrile) ether, lithium difluorophosphate and lithium tetrafluoroborate, and the above-mentioned electrolyte contains suitable components, the lithium ion battery can be further improved to have good low temperature discharge performance and short circuit test pass rate.

[0088] Table 5 In Table 5, the average sphericity of the silicon-carbon material and the mass percentage of lithium difluorophosphate in the electrolyte were adjusted to study their effects on the low-temperature discharge maintenance rate and short-circuit test pass rate of the lithium-ion battery. In Examples 4-1 to 4-11, when the average sphericity of the silicon-carbon material is within the above-mentioned suitable range and satisfies a specific relationship ratio with the mass percentage of lithium difluorophosphate, the lithium-ion battery can further improve good low-temperature discharge performance and short-circuit test pass rate.

[0089] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the scope of the technical solutions of the present application.

Claims

1. A secondary battery, comprising a negative electrode plate and an electrolyte, wherein the negative electrode plate comprises a negative electrode active material layer, characterized in that: The negative electrode active material layer comprises graphite and silicon-carbon material, and the average sphericity of the silicon-carbon material is 0.81 to 0.95; The electrolyte includes ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate. Based on the mass of the electrolyte, the mass percentage of ethylene carbonate is a%, the mass percentage of propylene carbonate is b%, the mass percentage of ethyl propionate is c%, and the mass percentage of propyl propionate is d%, wherein the range of (a+b) / (c+d) is 0.23 to 1.

51.

2. The secondary battery according to claim 1, characterized in that: The electrolyte further comprises 1,3,6-hexanetrinitrile. Based on the mass of the electrolyte, the mass percentage of the 1,3,6-hexanetrinitrile is e%, and the range of (a+b) / e is 4 to 18.

5.

3. The secondary battery according to claim 1, characterized in that: The electrolyte also includes at least one of fluoroethylene carbonate, succinonitrile, ethylene glycol bis(propionitrile) ether, lithium difluorophosphate or lithium tetrafluoroborate.

4. The secondary battery according to claim 3, characterized in that: Based on the quality of the electrolyte, the electrolyte satisfies at least one of the following conditions: (1) The mass percentage of the fluoroethylene carbonate is 0.5% to 3.9%; (2) The mass percentage of succinonitrile is 0.6% to 3.9%; (3) The mass percentage of the ethylene glycol bis(propionitrile) ether is 0.2% to 2.5%; (4) The mass percentage of the lithium difluorophosphate is 0.01% to 0.30%; (5) The mass percentage of the lithium tetrafluoroborate is 0.001% to 0.100%.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The electrolyte further comprises lithium difluorophosphate. Based on the mass of the electrolyte, the mass percentage of the lithium difluorophosphate is n%, and n and the average sphericity m of the silicon-carbon material satisfy the relationship: the range of m / n is 3 to 14.

5.

6. The secondary battery according to any one of claims 1 to 4, characterized in that: The electrolyte satisfies at least one of the following conditions: (1) a ranges from 10 to 38; (2) b ranges from 5 to 26; (3) c ranges from 12 to 26; (4) d ranges from 27 to 49.

7. The secondary battery according to claim 2, characterized in that: e ranges from 0.8 to 4.3, and / or (a+b) / e ranges from 5.1 to 15.

8. The secondary battery according to claim 7, characterized in that: e ranges from 1.3 to 3.

5.

9. The secondary battery according to claim 4, characterized in that: Based on the quality of the electrolyte, the electrolyte satisfies at least one of the following conditions: (1) The mass percentage of the fluoroethylene carbonate is 1.1% to 3.2%; (2) The mass percentage of succinonitrile is 1.3% to 3.2%; (3) The mass percentage of the lithium difluorophosphate is 0.04% to 0.24%; (4) The mass percentage of the ethylene glycol bis(propionitrile) ether is 0.4% to 2.1%; (5) The mass percentage of the lithium tetrafluoroborate is 0.008% to 0.050%.

10. The secondary battery according to claim 5, characterized in that: The m / n range is from 3.9 to 12.

7.

11. The secondary battery according to claim 6, characterized in that: The electrolyte satisfies at least one of the following conditions: (1) a ranges from 11 to 26; (2) b ranges from 7 to 20; (3) c ranges from 13 to 21; (4) The range of d is 30 to 44.

12. An electronic device, characterized in that: It includes the secondary battery according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Negative electrode material, secondary battery, and electronic device

    CN115312780A

  • Secondary battery and electronic device including the same

    CN117477039A

  • Silicon-based composite material, secondary battery, and electronic device

    CN118867163A

  • Etchant compositions and methods of manufacturing semiconductor device using the same

    KR1020250052943A

  • Electrochemical apparatus and electronic apparatus

    WO2022205110A1

Cited By

  • Electrolyte, secondary battery and electronic device

    CN119742460A

  • Secondary battery and electronic device

    WO2025256205A1

  • Electrolyte, secondary battery and electronic device

    WO2026184327A1